(untitled) (International Journal of Food and Nutritional Sciences, 2022)
With the development of technology, it is simple to recommend all of the frameworks in an approachable way. With the help of the Library Management Framework (LMS), traditional libraries can become computerised libraries. In traditional libraries, patrons/students must search for out-of-print books and there may not be proper maintenance of the data base on fines/issues. Since work is generally moving slowly forward, it is impossible to produce a report quickly. The custodians must show up prepared to organise and arrange the books in the book sales. They must simultaneously review and screen the loan/acquire book’s finer points. Working in multiple fields at once is a tedious cycle. The LMS will make it easier for the keepers to work